A survey on 5G/6G, AI, and Robotics. (October 2021) - Qiao, Liang; Li, Yujie; Chen, Dongliang; Serikawa, Seiichi; Guizani, Mohsen; Lv, Zhihan
Abstract: The development of various fields of computer is constantly improving people's lives. In recent years, the most obvious is the development of Artificial Intelligence (AI). Computer vision is applied to face recognition, natural language processing is applied to speech recognition, and machine learning is applied to data. Analysis and other typical application scenarios (He et al., 2019; Hosny et al., 2018; Yu et al., 2018 [1, 2, 3]). As the software part of robotics technology, artificial intelligence has become more and more mature. Recent research on robotics technology mainly centers on drones and assembly robots in intelligent manufacturing (Zhong et al., 2017; Egger and Masood, 2020; Chen, 2020 [4, 5, 6]). In addition to the above application scenarios, unmanned driving as the most important part of intelligent transportation is also a product of the combination of artificial intelligence and robots. In recent years, both academic and industrial aspects have conducted in-depth and extensive research on unmanned driving (Chen et al., 2019; Zhao et al., 2019 [7, 8]). Moreover, with the gradual commercial use of the fifth-generation mobile communication technology (5G), theoretical research on the sixth-generation mobile communication technology (6G) has also begun. Stronger mobile communication technology will make the information transmission in the intelligent transportation system more stable. It also improves the reliability of Intelligent Transportation Systems (ITS), which is the most important property. We believe that 5G/6G and artificial intelligence will be the two core technologies of the future intelligent transportation system, and these two fields will also receive extensive attention, which is very likely to produce breakthrough research results, so this paper The purpose is to summarize the current development of these two fields, and summarize the cross-research progress between them, and then discuss the bottleneck of the current development of intelligent transportation system and point out the future research direction. Graphical abstract: Highlights: A comprehensive overview of 5G/6G, AI, and Robotics. A collection of Federated Learning and Edge Intelligence. Potential research directions and applications in the field of 5G/6G and AI robots.